Research on basketball trends and evolution methodologies in countries with low popularity of the sport: The case of Portugal and the Compal Air (3v3) school tournament - Χατζηαυγουστίδης, Παναγιώτης (Πανεπιστήμιο Πελοποννήσου, 2015)
The scope of the current thesis is to analyze and understand the reason why basketball is a sport of low popularity in Portugal. Moreover, already applied strategies will be observed and ideas that could provide a greater level of help to the Portuguese Basketball Federation will be given. In the current study, the following entities agreed to participate: 17 out of 21 association managers and 11 club directors from teams that are currently active for the season of 2014-2015. More precisely, the clubs which participated in the survey are: 2 clubs from the female league (Vagos, Olivais), 1 from the female firstdivision (ADESCU), 3 from the male league (Clube do Povo de Esgueira, Benfica, Sampaense), 3 coming from the male pro- liga (Ginasio Cluba Figuerence, Texeira basket, Dragon Force), and 2 from the male first division (Academica, A.D. sanjoanense). While trying to figure out the state of sponsorship in the field of Portuguese Basketball, we came up to the conclusion that only the two biggest clubs of the country (Benfica and Porto’s Dragonforce) do actually have a professional marketing department. In the meanwhile, Academica from Coimbra is also doing small but steady step towards that direction. Within the current thesis, we researched the 3 on 3 Compal Air tournament and realized that is actually effective in attracting new -players, but not enough for the basketball philosophy. Lastly, after analyzing and plotting the survey results in SPSS, we gave replies to the initial research questions and proposed solutions to the existing problems.
Έρευνα πάνω στις τάσεις και μεθοδολογίες ανάπτυξης της καλαθοσφαίρισης σε χώρες με χαμηλή δημοτικότητα του αθλήματος: Η μελέτη περίπτωσης της Πορτογαλίας και του σχολικού τουερνουά (3x3) Compal Air
Keywords: Basketball; basketball popularity; Portugal; Καλαθοσφαίριση; Δημοτικότητα της καλαθοσφαίρισης; Πορτογαλία